How the local matters: Democratization in Libya, Pakistan, Yemen and Palestine - Louise Riis Andersen (Danish Institute for International Studies (DIIS), 2013)
The purpose of the study is to provide an overview of the core questions and dilemmas facing Denmark - and the wider international community - in applying a 'bottom-up' approach to democratisation in areas characterised by contested or limited statehood. In order to keep that discussion grounded, the study focuses on four individual cases that are highly different, yet equally complex: Libya, Pakistan, Yemen and Palestine. Each in their own way, they are all 'fragile'. Their national governments are experiencing severe difficulties in projecting their authority evenly across their territory. The particular circumstances and dynamics, however, differ tremendously: from the militarised fragility of Pakistan to the transitional state of Libya, the collapsing state of Yemen and the stateless state of Palestine. It clearly makes little sense to search for a common approach to reform in these four settings. At the same time, however, the individual cases suggest that the distinct operational challenges are in fact reflections of deeper tensions and dilemmas that stem from the paradox of using outside intervention to foster self-government (Paris and Sisk 2009). Against this shared backdrop, the present chapter summarises the findings of the four case studies and relates them to the generic policy discussion and experiences elsewhere. The chapter thus serves as both the introduction to and the conclusion of the entire study.
Keywords: 300